2018
DOI: 10.31072/rcf.v9i1.539
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de água com moringa oleífera como coagulante/floculante natural

Abstract: A aplicação da Moringa oleífera em pesquisas, testes e analises vem conquistando espaço. O presente trabalho busca por meio dessas pesquisas cientificas apontar uma nova forma de tratamento de água, utilizando a Moringa oleífera, como coagulante natural. Para utilizar a semente como coagulante, preparou-se uma solução leitosa extraída da mesma, o qual foi o meio utilizado para garantir o processo.  Diversos estudos apontam que os produtos produzidos por esta planta, trazem diversos benefícios para a saúde e pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…A positive feature of this study is that it was based on studies in Brazil and other countries in which the authors showed the effectiveness of moringa seeds in the treatment surface waters (13,23,26,27,28,29) . Furthermore, this study is a novel one as there are to our knowledge no studies on the use of moringa seeds with water from the Negro River in the São Gabriel da Cachoeira region.…”
Section: Discussionmentioning
confidence: 99%
“…A positive feature of this study is that it was based on studies in Brazil and other countries in which the authors showed the effectiveness of moringa seeds in the treatment surface waters (13,23,26,27,28,29) . Furthermore, this study is a novel one as there are to our knowledge no studies on the use of moringa seeds with water from the Negro River in the São Gabriel da Cachoeira region.…”
Section: Discussionmentioning
confidence: 99%
“…La M. Oleifera es una planta milagrosa, con enormes potencialidades (Adewumi & Samson, 2018). Lopes et al (2015), Oliveira et al (2018) y Keogh et al (2017) reportaron que la semilla de "moringa" tiene potencial como agente coagulante y puede ser utilizada como clarificador para diferentes tipos de aguas residuales con diversos grados de turbidez. En experimentos específicos, Lopes et al (2015) utilizaron aguas con diferentes grados de turbidez inicial (70, 250 y 400 NTU -unidades nefelométricas de turbidez), demostrando que el extracto de moringa logra remover la turbidez en un 89,5%, 95,5% y 97,5%, respectivamente.…”
Section: Introductionunclassified
“…Moringa oleifera seeds have positively charged proteins which allow it to attract negatively charged particles such as clays, silts, among others, forming clots/ floccles that later settle (Amagloh and Benang, 2009). This protein allows the reduction of the amount of microorganisms and suspended particles, resulting in the removal of turbidity, color and total coliforms without changing the pH (Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%